Reasons for ICU Demand and Long-term Follow-up of a Chronic Obstructive Pulmonary Disease Cohort. (1st December 2014) - Takir, Huriye Berk; Karakurt, Zuhal; Salturk, Cuneyt; Kargin, Feyza; Balci, Merih; Yalcinsoy, Murat; Ozmen, İpek and Yazicioglu, Ozlem Mocin and Gungor, Gokay and Burunsuzoğlu, Bünyamin and Adiguzel, Nalan
Abstract Acute respiratory failure (ARF) can necessitate mechanical ventilation and intensive care unit (ICU) admission in patients with COPD. We evaluated the reasons COPD patients are admitted to the ICU and assessed long-term outcomes in a retrospective cohort study in a respiratory level-III ICU of a teaching government hospital between November 2007 and April 2012. All COPD patients admitted to ICU for the first time were enrolled and followed for 12 months. Patient characteristics, body mass index (BMI), long-term oxygen therapy (LTOT), non-invasive ventilation (LT-NIV) at home, COPD co-morbidities, reasons for ICU admission, ICU data, length of stay, prescription of new LTOT and LT-NIV, and ICU mortality were recorded. Patient survival after ICU discharge was evaluated by Kaplan–Meier survival analysis. A total of 962 (710 male) patients were included. The mean age was 70 (SD 10). The major reasons for ICU admission were COPD exacerbation (66.7%) and pneumonia (19.7%). ICU and hospital mortality were 11.4%, 12.5% respectively, and 842 patients were followed-up. The new LT-NIV prescription rate was 15.8%. The 6-month 1, 2, 3, and 5-year mortality rates were 24.5%, 33.7%, 46.9%, 58.9% and 72.5%, respectively. Long-term survival was negatively affected by arrhythmia (p < 0.013) and pneumonia (p < 0.025). LT-NIV use (p < 0.016) with LTOT (p < 0.038) increase survival. Pulmonary infection can be a major reason for ICU admission and determining outcome after ICU discharge. Unlike arrhythmia and pneumonia, LT-NIV can improve long-term survival in eligible COPD patients.